1975
DOI: 10.1080/18811248.1975.9733074
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study of Steady-State Boiling of Sodium Flowing in a Single-Pin Annular Channel

Abstract: An experimental study was carried out on steady-state boiling of sodium flowing in the annular channel formed around a n electrically heated simulation of a fuel pin. In the present experiment, the inlet temperature and flow rate were held constant, and t h e heat flux was gradually increased up to t h e inception of boiling. Thereafter, the heat flux was further increased step by step until the surface temperature of the heater pin marked a sharp rise, indicating the occurrence of dry-out. Records were obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1977
1977
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…In addition, the liquid droplets were observed to deposit to the wall from a series of snapshots of X ray images [60]. Another experimental study on sodium boiling in a single-pin annular channel showed a similar flow pattern transitions from bubbly flow to slug flow and then to annular flow [61]. Therefore, it can be expected that the flow patterns inside a heat pipe for liquid metals and for low-temperature fluids will also be similar.…”
Section: High-temperature Working Fluidsmentioning
confidence: 99%
“…In addition, the liquid droplets were observed to deposit to the wall from a series of snapshots of X ray images [60]. Another experimental study on sodium boiling in a single-pin annular channel showed a similar flow pattern transitions from bubbly flow to slug flow and then to annular flow [61]. Therefore, it can be expected that the flow patterns inside a heat pipe for liquid metals and for low-temperature fluids will also be similar.…”
Section: High-temperature Working Fluidsmentioning
confidence: 99%
“…To investigate the onset and propagation of sodium boiling within pin bundles, various experiments have been carried out by different authors. Some of previous experimental investigations of sodium boiling are Kikuchi et al, [1], Khafizov et al [2], Qiu et al [3], Zicheng et al [4] and Katsuro et al [5]. But since sodium experiments are expensive and involve safety concerns, large volumes of numerical simulations were also reported on sodium boiling.…”
Section: Introductionmentioning
confidence: 99%
“…The upper boundary of gas volume fraction has been chosen according to work [1,2]. To calculate the interphase friction coefficients, the following relation are used:…”
Section: Description Of the Models To Calculate Processes In Two-phasmentioning
confidence: 99%
“…So it is important to provide numerical and experimental investigations of the motion of bubbles in liquid metals. During the sodium boiling in core or during the leakage in steam generator slug regime is the main two-phase [1,2]. The feature of slug flow regime is the existence of sharp boundary between phases that make some difficulties to numerical simulating especially in one dimensional approximation.…”
Section: Introductionmentioning
confidence: 99%